Development of modeling methods and algorithm for calculating the current-voltage characteristics of LED modules - Shynkarenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Current-voltage characteristics of real high-power LED chips and their defects were studied. Process of modeling LED matrix by using Monte Carlo method based on the measured real LED chips was considered and performed. It was shown that the risk of variating LED chip parameters for stability of a final LED matrix as a result of the non-uniform heating up of individual elements in a series-parallel circuit. The solution allowing to significantly reducing the influence of LED chips input parameters variationon the final parameters of LED matrix was proposed.